Safety of Anti-TNF-Alpha Therapy During Pregnancy on Long-term Outcome of Exposed Children: A Controlled, Multicenter Observation - Duricova, Dana; Dvorakova, Eva; Hradsky, Ondrej; Mitrova, Katarina; Durilova, Marianna; Kozeluhova, Jana; Kohout, Pavel; Zarubova, Kristyna; Bronsky, Jiri; Hradska, Nora; Bronska, Eva; Adamcova, Miroslava; et al. (Inflammatory bowel diseases, 2019)
BACKGROUND: Evidence of the impact of in utero exposure to anti-tumor necrosis factor (TNF)-alpha on long-term childhood development is limited. The aim was to assess the impact of in utero exposure to anti-TNF-alpha due to mothers' inflammatory bowel disease (IBD) on long-term postnatal development of exposed children. METHODS: We included consecutive children (≥12 months of age) born to mothers with IBD (2007-2016) treated with anti-TNF-alpha during pregnancy in 3 centers in the Czech Republic. A control group was comprised of unexposed children of non-IBD mothers undergoing mandatory check-ups at general pediatricians' offices. Data on perinatal period, psychomotor development, vaccination, infections, antibiotics, and allergy were collected by treating pediatricians using a predefined questionnaire. RESULTS: Seventy-two exposed and 69 unexposed children were included (median age, 35 and 50 months, respectively). Exposed children had growth and psychomotor development similar to controls. There was no significant difference in infectious complications within the first year of life (23.9% vs 17.4%; P = 0.36) or during the whole follow-up between exposed infants and controls (P = 0.32). Concomitant immunosuppressants during pregnancy and anti-TNF-alpha levels in cord blood were not associated with elevated infection rate within the first year of life (P > 0.05). Over 95% of exposed children had adequate serologic response to vaccination, except for haemophilus and mumps vaccines. Clinically manifested allergy was similar between the groups (P = 0.98). CONCLUSIONS: Anti-TNF-alpha exposure in utero does not seem to have a negative impact on postnatal development of children with regard to infectious complications, allergy, growth, or psychomotor development when compared with unexposed children of non-IBD women.
Keywords: Infliximab; Infant; Humans; Pregnancy; zpožděný efekt prenatální expozice; Case-Control Studies; kojenec; dítě; studie případů a kontrol; kohortové studie; Child; infliximab; infections; Female; Gastrointestinal Agents; inflammatory bowel disease; children; Inflammatory Bowel Diseases; lidé; Pregnancy Complications; adalimumab; Adalimumab; TNF-alfa; Cohort Studies; předškolní dítě; idiopatické střevní záněty; Follow-Up Studies; ženské pohlaví; Male; prognóza; těhotenství; komplikace těhotenství; Tumor Necrosis Factor-alpha; gastrointestinální látky; Prenatal Exposure Delayed Effects; anti-TNF-alpha; vaccination; matky; mužské pohlaví; Child, Preschool; Prognosis; následné studie; Mothers